2015
DOI: 10.1039/c5sm01841b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly protocol design for periodic multicomponent structures

Abstract: Assembling molecular superstructures with many distinct components will allow unprecedented control over morphology at the nanoscale. Recently, this approach has been used to assemble periodic structures with precisely defined features, such as repeating arrays of pores and channels, using a large number of building blocks. Here we propose a predictive tool that allows us to optimize the nucleation and growth of unbounded, ordered structures. In what follows, we call these structures 'crystals', even though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
(64 reference statements)
0
33
0
Order By: Relevance
“…15 By tuning their pairwise interactions, nano- and microscale colloids can be assembled into a myriad of morphologies with even greater complexity than those found in atomic systems. 6,7 The vast phase space of parameters governing the mathematical form of these potential interactions can be daunting, and determining specific pair potentials that stabilize a desired structure is rarely obvious.…”
Section: Introductionmentioning
confidence: 99%
“…15 By tuning their pairwise interactions, nano- and microscale colloids can be assembled into a myriad of morphologies with even greater complexity than those found in atomic systems. 6,7 The vast phase space of parameters governing the mathematical form of these potential interactions can be daunting, and determining specific pair potentials that stabilize a desired structure is rarely obvious.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to systems with only a few components, the only way to achieve full assembly is to use a cooling protocol, where the system first crosses the nucleation barrier to a partially formed assembly, and further cooling stabilises the full assembly. While our calculations are quantitative for a specific 334 strand SST system, a number of the basic qualitative results above are also found with simpler models [20][21][22][23][24][25] and are likely to generically hold for a wider range of target structures [8][9][10][11][12][13][14] that use the addressable SST assembly method.…”
Section: Discussionmentioning
confidence: 76%
“…More recently, this model was used to investigate strategies to optimise nucleation and growth of unbounded, periodic structures. 25 Another strand of research into addressable assembly, also using simplified models, 26 has suggested that using carefully chosen non-stoichiometric abundances of assembly components may help to mitigate aggregation and undesirable monomer starvation effects.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the formation of a structure must be initiated by a nucleation event ('nucleation'). Due to cooperative or allosteric effects in binding, there might be a significant nucleation barrier [15][16][17][18][19] . Third, following nucleation, structures grow via aggregation of substructures ('growth').…”
Section: Introductionmentioning
confidence: 99%